Terapias farmacológicas tradicionais e práticas integrativas e complementares em saúde no manejo do Transtorno de Déficit de Atenção e Hiperatividade (TDAH) - (:unkn) unknown (ICET - Instituto de Ciências Exatas e Tecnologia (Itacoatiara), 2026)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a highly prevalent neurodevelopmental disorder that, due to the recurrence of symptoms such as inattention, hyperactivity, and impulsivity, produces significant impacts on the social, academic, and emotional domains of children and adolescents. This study aimed to evaluate the integrated use of Traditional Pharmacological Therapies and Integrative and Complementary Health Practices (ICHP), seeking to compare their benefits, limitations, and efficacy. A systematic search for studies addressing Pharmacological Therapies and ICHP in ADHD initially identified 149 articles. After screening and exclusion of duplicates and non-eligible studies, 26 were selected for the final analysis, as they met all inclusion criteria. The analysis revealed that although the diagnosis of ADHD is clinical (DSM-5) and multidisciplinary, it has led to increasing medicalization. First-line pharmacotherapy is widely used, with psychostimulants such as Methylphenidate (MPH) and Lisdexamfetamine (LDX) being the most prominent and non-stimulant drugs such as Atomoxetine (ATX) which are considered second-line treatment. These agents demonstrated strong efficacy by blocking the reuptake of dopamine and norepinephrine, resulting in improved concentration and reduced hyperactivity. However, their effectiveness requires rigorous monitoring due to potential adverse effects (such as insomnia, anxiety, and cardiovascular issues). Among the two main stimulants, LDX is frequently reported to have a longer duration of action and possibly better tolerability. Given the limitations of purely pharmacological treatment, the study confirmed the value of ICHP. These practices, recognized and freely provided by the Brazilian Unified Health System (SUS) through the National Policy on Integrative and Complementary Practices (PNPIC), emerge as a holistic and humanized adjuvant alternative. The findings indicate that ICHP provide significant benefits by helping manage associated symptoms (such as stress and anxiety) and, in some cases, reducing the need for high doses of psychostimulants. The overall consensus of the study points to the combined approach as the most promising strategy. The integrated use of pharmacological therapy (for immediate control of core symptoms) and ICHP (for comprehensive care and improved quality of life) maximizes efficacy and enhances patient adherence. Within this integrated model, the pharmacist emerges as a crucial link. Their role, regulated by the Federal Council of Pharmacy (CFF), ensures pharmacological safety (strict dispensing and guidance on adverse effects) and promotes holistic care through the application and orientation of ICHP. In conclusion, this research confirms the efficacy of psychostimulants and the complementary value of ICHP. However, to consolidate treatment individualization, continuous multidisciplinary research is imperative to address the current lack of specificity in evidence regarding ICHP, ensuring increasingly safe, effective, and patient-centered treatments for individuals with ADHD.
Traditional pharmacological therapies and integrative and complementary health practices in the context of Attention-Deficit/Hyperactivity Disorder (ADHD)
Keywords: TDAH; Terapias farmacológicas; Práticas integrativas e complementares em saúde; Crianças; Farmacêutico; ADHD; Pharmacological therapies; Integrative and complementary health practices; Children; Pharmacist; CIENCIAS DA SAUDE: FARMACIA; .; .; .